A Humanized Anti-Interleukin 6 Receptor Monoclonal Antibody, Tocilizumab, for the Treatment of Endometriosis in a Rat Model. (May 2016) - Taskin, Mine Islimye; Gungor, Aysenur Cakir; Adali, Ertan; Yay, Arzu; Onder, Gozde Ozge; Inceboz, Umit
Objective: The aim of this study was to investigate the efficacy of anti-interleukin 6 (IL-6) therapy in the treatment of endometriosis in a rat model. Study Design: After the peritoneal implantation of autologous endometrial tissue, 22 Wistar female rats were divided to create 2 intervention groups: the tocilizumab group (n = 13) and the control group (n = 9). After measuring implant volume, saline was administered to the rats in the control group and 8 mg/kg tocilizumab was administered intraperitoneally to the rats in the tocilizumab-treated group every 2 weeks. After a 4-week treatment period, the volumes and histopathological properties of the implants were evaluated. A scoring system was used to evaluate the preservation of epithelia. Fibrosis score was assessed between the groups. Ectopic and eutopic endometrium were evaluated immunohistochemically for IL-6 and vascular endothelial growth factor (VEGF). Results: There was a significant difference between the volumes of implants before and after treatment in the tocilizumab group ( P < .05). The posttreatment volumes of lesions were smaller in the tocilizumab group than in the control group. Histologic and fibrosis scores were lower in the tocilizumab group than in the control group. Immunoreactivity intensity for VEGF was significantly decreased in the tocilizumab group for ectopic and eutopic endometrium ( P < .05). Interleukin 6 levels and endometrial thickness for ectopic and eutopic endometrium were similar between the groups. Conclusion: Tocilizumab treatment had a regressive effect on the endometriotic implants.